Spatio-temporal genetic structure of the striped field mouse (Apodemus agrarius) populations inhabiting national parks in South Korea: Implications for conservation and management of protected areas - Kim, Yu Rim; Kim, Hye Ri; Kim, Ji Young; Myeong, Hyeon Ho; Kang, Ji Hyoun; Kim, Baek-Jun; Lee, Hyuk Je (Frontiers in Ecology and Evolution, 2023)
Population or habitat connectivity is a key component in maintaining species and community-level regional biodiversity as well as intraspecific genetic diversity. Ongoing human activities cause habitat destruction and fragmentation, which exacerbate the connectivity due to restricted animal movements across local habitats, eventually resulting in the loss of biodiversity. The Baekdudaegan Mountain Range (BMR) on the Korean Peninsula represents 'biodiversity hotspots' and eight of the 22 Korean national parks are located within the BMR. Given the striped field mouse (Apodemus agrarius) is the most common and ecologically important small mammals in these protected areas, the population genetic assessment of this species will allow for identifying ‘genetic diversity hotspots’ and also ‘genetic barriers’ that may hinder gene flow, and will therefore inform on effective conservation and management efforts for the national park habitats. We collected samples from hair, tail, or buccal swabs for 252 A. agrarius individuals in 2015 and 2019. By using mitochondrial DNA cytochrome b (cyt b) sequences and nine microsatellite loci, we determined levels of genetic diversity, genetic differentiation, and gene flow among eight national park populations of A. agrarius along the BMR. We found high levels of genetic diversity but the occurrences of inbreeding for all the nine samples analyzed. Our results also indicated that there was detectable temporal genetic variation between the 2015 and 2019 populations in the Jirisan National Park, which is probably due to a short-term decline in genetic diversity caused by reduced population sizes. We also found a well-admixed shared gene pool among the national park populations. However, a significant positive correlation between geographic and genetic distances was detected only in mtDNA but not microsatellites, which might be attributed to different dispersal patterns between sexes. There was a genetic barrier to animal movements around the Woraksan National Park areas. The poor habitat connectivity surrounding these areas can be improved by establishing an ecological corridor. Our findings of the presence of genetic barriers in some protected areas provide insights into the conservation and management efforts to improve the population or habitat connectivity among the national parks.